2020
DOI: 10.1016/j.ijid.2020.05.118
|View full text |Cite
|
Sign up to set email alerts
|

Combination of thrombolytic and immunosuppressive therapy for coronavirus disease 2019: A case report

Abstract: In a proportion of patients, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a multisystem syndrome characterized by hyperinflammation, acute respiratory distress syndrome (ARDS), and hypercoagulability. A 68-year-old man with coronavirus disease 2019 (COVID-19) was admitted to the intensive care unit with respiratory failure, cytokine release syndrome (CRS), and skin ischemiamicrothrombosis. Specific coagulation and inflammatory markers (D-dimer, ferritin, and Creactive protein), along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Our COVID-19 patient developed ACP and had high values of ferritin, C-reactive protein, hypercapnia, and alveolar dead space; all of these parameters were reduced after rtPA treatment. In the line with our findings, Papamichalis et al reported reduced levels of ferritin and C-reactive protein following the administration of rtPA and tocilizumab ( Papamichalis et al, 2020 ). Hypercapnia has also been linked with the development of ACP and is thought to represent one of the factors responsible for vasoconstriction and the augmentation of pulmonary arterial pressure ( Jardin and Vieillard-Baron, 2009 , Biswas, 2016 , Boissier et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our COVID-19 patient developed ACP and had high values of ferritin, C-reactive protein, hypercapnia, and alveolar dead space; all of these parameters were reduced after rtPA treatment. In the line with our findings, Papamichalis et al reported reduced levels of ferritin and C-reactive protein following the administration of rtPA and tocilizumab ( Papamichalis et al, 2020 ). Hypercapnia has also been linked with the development of ACP and is thought to represent one of the factors responsible for vasoconstriction and the augmentation of pulmonary arterial pressure ( Jardin and Vieillard-Baron, 2009 , Biswas, 2016 , Boissier et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…This is likely attributable to presenting location/etiology of ischemia and the degree to which symptoms developed. The most common medical 8 while in two other cases tocilizumab was used in addition to antibiotics and antivirals with and without anticoagulation respectively. 5 Other immunotherapy medications such as glucocorticoids and IgG were described as well with some success.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue plasminogen activators (TPA), antihemophilic factors, immune globulin, and anti-thymocyte globulin are found to be good candidates in COVID-19 treatment as per our various omics-based analyses. Reports suggest that, TPA with targeted anti-inflammatory treatment may be a potential therapy against COVID-19 [ 38 ]. Tenecteplase, a TPA, that is identified in our analysis, is considered in managing acute coronary syndromes associated with COVID-19 [ 39 ] and is currently under clinical trial to manage COVID-19 patients (NCT04505592).…”
Section: Discussionmentioning
confidence: 99%